Oral Supplementation with Beta-Hydroxy-Beta-Methylbutyrate, Arginine, and Glutamine Improves Lean Body Mass in Healthy Older Adults. (4th May 2019) - Ellis, Amy C.; Hunter, Gary R.; Goss, Amy M.; Gower, Barbara A.
ABSTRACT: Oral intake of beta-hydroxy-beta-methylbutyrate (HMB), arginine, and glutamine may ameliorate muscle loss by stimulating protein synthesis and decreasing protein degradation while simultaneously decreasing inflammation. Previous studies provide evidence for improvement in body composition with dietary supplementation of these ingredients among patients with muscle-wasting diseases. The objectives of this study were to examine the effects of this amino acid mixture on lean body mass, muscle volume, and physical function among healthy older adults. Thirty-one community-dwelling men and women, aged 65–89 years, were randomized to either two oral doses of the amino acid supplement (totaling 3 g HMB, 14 g arginine, 14 g glutamine) or placebo daily for six months. At baseline and month six, lean body mass was measured by air displacement plethysmography, dual-energy X-ray absorptiometry (DXA), and four-compartment model. Muscle volume of quadriceps was quantified by magnetic resonance imaging (MRI), and participants performed a battery of tests to assess physical function. As compared to the placebo group, the treatment group exhibited improvement in a timed stair climb ( p =.016) as well as significant increases in lean body mass by all methods of assessment ( p <.05). Regional analysis by DXA revealed increased arm lean mass in the supplement group only ( p =.035). However, no change was observed in MRI-derived quadriceps volume. Dietary supplementation with HMB, arginine, and glutamine improved total body lean mass among a small sample of healthy older adults. Further research is indicated to elucidate mechanisms of action and to determine whether supplementation may benefit frail elders. Registered under ClinicalTrials.gov identifier no. NCT01057082.